Red blood cell prescription and recognition of transfusion reactions by pediatricians - Schaffhausser Filho,Carlos João (2020)
ABSTRACT Objective To assess the level of knowledge of emergency pediatricians on red blood cell transfusions and their reactions. Methods Written survey with emergency pediatricians from a pediatric hospital. Results Less than 20% of pediatricians showed appropriate knowledge on prescribing red blood cells and recognition of transfusion reactions. There was no significant statistical regarding time since graduation and blood transfusion classes in undergraduate studies or during medical residency. Conclusion Pediatricians have insufficient knowledge about red blood cell transfusions and recognition of transfusion reactions.